دراسة بواسطة الطبقي المحوري المحوسب لطول وعمق قبة الحنك الصلب وعلاقتهما مع نموذج النمو الوجهي لدى البالغين(دراسة بواسطة الطبقي المحوري المخروطي) - حسن, حازم (Latakia University Journal -Medical Sciences Series, 2016)
It is generally agreed that growth in palatine results from bone formation at the palatine sutures and lengthening of the alveolar processes, but the extent to which these two sites contribute to the depth and length of the hard palate remains unsolved. Hence, professionals should use quantitative assessments of the hard palate, which allow more accuracy in the diagnosis and assessment of this structure. Aim investigating the relationship between the length and depth of the skeletal hard palatine with facial growth type in adult subjects using CBCT scan. Materials and methods: 20 Caucasian patients (8 males, 12 females) from 18 to 23 years of age, (mean age of 22.13 years), were chosen from pretreatment patients undergoing orthodontic evaluation at the Department of Orthodontics and Dentofacial Orthopedics at Tishreen University. They were ordinarily undergoing CBCT scan for non-orthodontics and not for otolaryngology purpose. Cephalometric growth study was performed according to Jarabak. Pearson's Correlation Coefficient was calculated to investigate the relation between the hard palatine length and depth with facial growth type. Results: The studied CBCT hard palatine measurements have no statistical significance between the two genders; CBCT hard palatine length and depth have no relationship with facial type growth. Conclusion: Palatine depth and length do not seem to obey any specific growth type.من المعلوم إنه نمو الحنك عموماً هو نتيجة للتشكل العظمي للدروز الحنكية وتطاول النتوءات السنخية، إلا إنه من غير المعروف بدقة مدى العلاقة المتبادلة ما بين عمليتي النمو هاتين، وبين عمق وطول قبة الحنك الصلب، من هنا فإنه يتوجب على الإختصاصيين اللجوء إلى تقييم قبة الحنك الصلب قابل للقياس مما يسمح بوضع تشخيص أكثر دقة ويساعد الممارس في تقييم أفضل لهذه البنية التشريحية.هدف البحث: دراسة العلاقة بين طول وعمق قبة الحنك الصلب مع النمو الوجهي وذلك لدى أفراد من البالغين باستخدام التصوير الطبقي المخروطي.مواد وطرق البحث: أفراد العينة 20 بالغ من العرق قوقازي (8 ذكور،12 أنثى) بعمر ما بين 18 إلى 23 (متوسط العمر 22.13 سنة) من مراجعي قسم تقويم الأسنان والفكين بكلية طب الأسنان بجامعة ولم يخضعوا لمعالجة تقويمية سابقة حيث تم انتقائهم من مرضى كانوا تلقائياً بصدد إجراء تصوير طبقي محوري مخروطي لأسباب لا تتعلق بمشاكل تقويمية أو بأمراض الأنف والأذن والحنجرة، تم إجراء دراسة سيفالومترية للنمو الوجهي وفق جاراباك، ومن ثم تحليل معامل ارتباط بيرسون لدراسة العلاقة بين طول وعمق قبة الحنك الصلب مع النمو الوجهي مع القياسات السيفالومترية المحددة للنمو الوجهي حسب جاراباك.النتائج: لا توجد فروقات ذات دلالة إحصائية في قياسات الطبقي المحوري المخروطي لقبة الحنك الصلب المدروسة بين الجنسين في العينة المدروسة، طول وعمق قبة الحنك الصلب لا يمتلكان علاقة ذات دلالة إحصائية مع النماذج النمو الوجهي.الخلاصة: كلا من طول وعمق قبة الحنك الصلب لا يرتبطان مع نموذج نمو وجهي محدد.